Non-infectious fluorimetric assay for phenotyping of drug-resistant HIV proteinase mutants - Majerová-Uhlíková, Tat'ána; Dantuma, Nico P; Lindsten, Kristina; Masucci, Maria G; Konvalinka, Jan (Journal of clinical virology, 2006)
BACKGROUND: The introduction of HIV proteinase inhibitors (PIs) as anti-AIDS drugs resulted in decreased mortality and prolonged life expectancy of HIV-positive patients. However, rapid selection of drug-resistant HIV variants is a common complication in patients undergoing highly active anti-retroviral therapy (HAART). Thus, monitoring of clinical resistance development is indispensable for rational pharmacotherapy. OBJECTIVE: We present a non-infectious cell-based assay for drug resistance quantification of HIV proteinase (PR) - an important target of HAART. STUDY DESIGN: Previously, we showed [Lindsten K, Uhlikova T, Konvalinka J, Masucci MG, Dantuma NP. Cell-based fluorescence assay for human immunodeficiency virus type 1 protease activity. Antimicrob Agents Chemother 2001;45:2616-22] that the expression of a fusion protein (GFP-PR), comprised of HIV-1 proteinase wild-type artificial precursor (PR) and green fluorescent protein (GFP), in transiently transfected tissue culture cells depends on the presence of PR-specific inhibitors (PIs). Here we show that in the GFP-PR reporter the HIV wild-type PR can be replaced by a drug-resistant HIV PR mutant, yielding a simple and biologically relevant tool for the quantitative analysis of drug-resistant HIV PR mutants susceptibility to HIV proteinase inhibitors. RESULTS: We cloned a set of GFP-PR reporters, some of which possess a simple, well-defined drug-resistant PR mutant (G48V L90M, V82A, A71V V82T I84V, D30N, K45I); another four complex PR mutants were obtained from patients undergoing HAART. The results were compared with genotyping and enzyme kinetics data. Furthermore, we designed a single inhibitor concentration experiment setup for easy evaluation of drug resistance profiles for mutants of interest. The resistance profiles clearly demonstrate the importance of succession of individual drugs during the treatment for drug resistance development. CONCLUSION: We show that the GFP-PR assay might serve as a non-infectious, rapid, cheap, and reliable alternative to the currently used phenotypic assays.
Keywords: transfekce; inhibitory HIV-proteasy; Evaluation Studies as Topic; Fluorometry; fenotyp; monoklonální protilátky; Phenotype; mutace; Plasmids; Recombinant Fusion Proteins; hodnotící studie jako téma; Transfection; fluorescenční mikroskopie; Cloning, Molecular; western blotting; reportérové geny; klonování DNA; vztah mezi dávkou a účinkem léčiva; Biological Assay; HIV Protease Inhibitors; rekombinantní fúzní proteiny; biotest; Flow Cytometry; HeLa buňky; Blotting, Western; kinetika; zelené fluorescenční proteiny; průtoková cytometrie; Drug Resistance, Viral; lidé; HIV Protease; Microscopy, Fluorescence; fluorometrie; HeLa Cells; Humans; HIV-proteasa; plazmidy; Green Fluorescent Proteins; spektrofotometrie; virová léková rezistence; Spectrophotometry; Antibodies, Monoclonal; Mutation; Genes, Reporter; virové geny; Dose-Response Relationship, Drug; Kinetics; Genes, Viral